تقييم مستوى التلوث بالمكورات العنقودية الذهبية في غرف العمليات بمركز مصراتة الطبي (Journal of Academic Research, 2025)
This study was conducted to assess the microbial contamination of the Staphylococcal Aureus bacteria in the operating theatres of Misrata Medical Centre by taking 160 swabs of some medical tools, equipment, and floors from July 2022 to January 2023. The study findings demonstrated that there was a 7.89% contamination rate before the Staphylococcal Aureus bacteria sterilisation and a 0% contamination rate following the sterilisation.     The staphylococcal aureus bacteria appeared before sterilisation in the Orthopaedic department operating room at 5.26% and 2.63% in the Neurosurgery department before sterilisation, but none occurred in the other departments. A high rate of contamination emerged after sterilisation, with Gram-negative Baccilli at 18.42%, followed by Gram-positive Baccilli at 10.53%. Staphylococcus Haemolyticus and Klebsiella Pneumonia were the most common species at 7.89%.    The bacteria spread among the four operating rooms, with the Emergency department having the largest percentage (18.41%), followed by General Surgery (10.52%) and Orthopaedics (7.89%). The Neurosurgery department had the lowest percentage (2.63%).       The study also revealed variations in the rates of bacterial contamination among the sampling sites. The shoes of the workers had the highest rate of contamination (19.4%), followed by the suction machines (13.9%), the anaesthesia machines and clips (2.8%), and the scissors and forceps (no rate). Additionally, the isolated Gram-positive Bacilli bacteria tested highly resistant to Ampicillin, Pencillin G, and Oxacillin when tested using the DB phoenix diagnostic device and 22 different antibiotic types.